2022
DOI: 10.1111/aor.14151
|View full text |Cite
|
Sign up to set email alerts
|

Designer organs: The future of personalized transplantation

Abstract: Organ transplantation is the definitive treatment for end‐stage solid organ diseases, yet biological and logistical barriers reduce the rate of successful organ transplants. As such, there is a need for gene therapy and gene modulation strategies in the organ transplantation setting to prevent rejection, expand the donor pool of available organs, and attenuate ischemia‐reperfusion damage. As we are entering an era of “precision medicine,” the organ transplant field is becoming equipped with the tools necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 99 publications
(160 reference statements)
0
6
0
Order By: Relevance
“…Xenotransplantation with pigs as source of donor kidneys 92–97 is progressing from experimental studies from pig‐to‐non‐human primates (NHP) to clinical trials with brain‐dead patients. An excellent review on the state‐of‐the‐art of porcine kidney xenotransplantation has been published recently by Cooper et al 93,98 The most important prerequisite for xenotransplantation of porcine organs is the knockout of genes encoding for xenoantigens particularly galactose‐α1, 3‐galactose and other pig cell surface antigens eliciting a strong immune response in primates 98,99 .…”
Section: Alternative Technologies For Detoxification and Development ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Xenotransplantation with pigs as source of donor kidneys 92–97 is progressing from experimental studies from pig‐to‐non‐human primates (NHP) to clinical trials with brain‐dead patients. An excellent review on the state‐of‐the‐art of porcine kidney xenotransplantation has been published recently by Cooper et al 93,98 The most important prerequisite for xenotransplantation of porcine organs is the knockout of genes encoding for xenoantigens particularly galactose‐α1, 3‐galactose and other pig cell surface antigens eliciting a strong immune response in primates 98,99 .…”
Section: Alternative Technologies For Detoxification and Development ...mentioning
confidence: 99%
“…Xenotransplantation with pigs as source of donor kidneys [92][93][94][95][96][97] is progressing from experimental studies from F I G U R E 4 Scheme of an implantable artificial kidney (IAK). The iliac vessels are used as intake of the arterial blood and outlet for the venous blood, while the removed waste is shunted to the bladder.…”
Section: Brief Survey On Alternative Approaches To Solve the Problem ...mentioning
confidence: 99%
“…Knocking out the GGTA 1 gene will not only significantly increase the survival length of the patients after the transplantation up to 6 months, but will also highly reduce the hyperacute rejections, as studies of xenotransplantation in baboons suggested [28,29]. Moreover, hyperacute rejection can be further reduced by expression of human complement regulatory proteins such as CD46, CD55, or CD59 together with the GGTA1 deletion [30][31][32]. A more advanced method which is to remove two xeno antigens which are α-Gal and N-glycolylneuraminic acid also can be combined, as it will further reduce the humoral activity compared to a GGTA1 knockout alone [16].…”
Section: B Solution To Solve the Problemmentioning
confidence: 99%
“…Among many approaches to ameliorate immune activation of the graft 22 , gene therapy is very appealing because it can specifically target pathways 23,24 , by treating the donor or the graft. Genetic manipulation of donor organs may render grafts more resistant to IRI, reduce immunogenicity and the requirement for systemic immunosuppression, thus promoting long-term graft survival 25 . The combination of gene therapy/modulation during ex-situ organ preservation is relatively new but very promising because it offers a controlled environment and avoid systemic therapy 10 .…”
Section: Gene Therapy Strategies In Organ Transplantationmentioning
confidence: 99%